Mewaspadai jebakan reifikasi dalam wajah industrialisasi niretika lingkungan dan kebakaran hutan - Santoso, Bambang; Rustamaji, Muhammad (PROGRESIF: Jurnal Hukum, 2019)
Human being and living quality of their global community very depends on environmental condition. Then, various policies, regulation managements, law enforcement and technical supervision are conducted in attempts of biological environment conservation. However, a single market of such the global industrialization style gives a complex homework in ecological sector. On the Markplus Conference 2015, Hermawan Kartajaya reminded that the global industrialization, like the single market initiated by the AEC is potentially more dangerous than the AFTA (ASEAN Free Trade Area) and CAFTA (China-ASEAN Free Trade Agreement). He stated that if AFTA and CAFTA are concerned only with flow of goods, but MEA covers free flow of goods, people, services and money (capital and investment). Purpose of the writing is actually to show challenges that should be addressed when MEA establishes a single ASEAN market, especially be related to forest fire’s phenomenon. Results of the study showed that forest fire and the single ASEAN market has, consciously or not, created a new myth called rationality of commodity efficiency. Horkheimer and Adorno in their ' enlightenment dialectic' explained that efficiency, in economic, is a principle of market surpassing all kinds of feudal and religious restrictions. Thus, rationality is equated with efficiency. When efficiency is applied in dynamics of capitalist economy, then the entire field of human life is considered a commodity. Consequently, reification is in effect, namely when everything is a commodity so people is no longer enjoying but consuming and consuming without building any social relationships in a real sense. At such nadir, ecological damage is inevitable or it is even considered a reasonable price worth paying. The Law which is essentially an ethical conversation of human beings to produce justice is easily forgotten because of greed. However, all such excesses of reification can be avoided when the law is still pursued progressively, so the law must arrive at radicalism in order to demolish assumptions of law. Thus, it can be concluded that forest should not only be explored for its resources solely according to the reification trap of global industrialization market, but it must be preserved for future human posterity because of considering the deep ecology.